2015
DOI: 10.1016/j.envres.2015.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Associations of maternal organophosphate pesticide exposure and PON1 activity with birth outcomes in SAWASDEE birth cohort, Thailand

Abstract: Prenatal organophosphate (OP) pesticide exposure has been reported to be associated with adverse birth outcomes and neurodevelopment. However, the mechanisms of toxicity of OP pesticides on human fetal development have not yet been elucidated. Our pilot study birth cohort, the Study of Asian Women and Offspring’s Development and Environmental Exposures (SAWASDEE cohort) aimed to evaluate environmental chemical exposures and their relation to birth outcomes and infant neurodevelopment in 52 pregnant farmworkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 59 publications
2
48
2
1
Order By: Relevance
“…Paraoxonase ( PON1 ) is known to detoxify organophosphate (OP) pesticides [ 17 ], and depending on the gene polymorphism, can modify the effects of OP exposure [ 18 ]. Two specific PON1 polymorphisms ( − 108 and 192 ) have been implicated as potential modifiers of the association between OP pesticide exposure and poor birth and childhood health outcomes, including reduced birth weight, shortened length of gestation, and neurobehavioral issues [ 19 , 20 , 21 , 22 ]. Other studies have investigated the link between diet and asthma exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…Paraoxonase ( PON1 ) is known to detoxify organophosphate (OP) pesticides [ 17 ], and depending on the gene polymorphism, can modify the effects of OP exposure [ 18 ]. Two specific PON1 polymorphisms ( − 108 and 192 ) have been implicated as potential modifiers of the association between OP pesticide exposure and poor birth and childhood health outcomes, including reduced birth weight, shortened length of gestation, and neurobehavioral issues [ 19 , 20 , 21 , 22 ]. Other studies have investigated the link between diet and asthma exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…HDL also carries paroxonase. As with apoA‐I, lower paroxonase activity has been associated with adverse pregnancy outcomes (48). HDL also transports cholesterol between tissues and can result in removal of cholesterol from membranes or in deposition of cholesterol into cells leading to changes in membrane‐based signaling [reviewed by Fielding and Fielding (49)].…”
Section: Discussionmentioning
confidence: 99%
“…Reiss [80] found out that the critical exposure period to PO insecticides for human neurological development is, by definition, the only relevant exposure for birth outcomes. Naksen et al [81] reported that the birth outcomes as a result of OP exposure suggest a decrease in birth weight and head circumference in newborns born from mothers with low PONI activity.…”
Section: Organochlorine Pesticides (Ocps)mentioning
confidence: 99%